The Pesanggrahan Krapyak Giriwoyo: Identifikasi Kerusakan dan Strategi Penanganannya - Hery Priswanto; Irfanuddin Wahid Marzuki; Muhammad Chawari; Baskoro Daru Tjahjono; R. Adi Deswijaya; Atik Ardiati (Berkala Arkeologi, 2023)
Pesanggrahan Krapyak Giriwaya is one of the buildings inherited from Kasunanan Surakarta Hadiningrat built by Sri Susuhunan Pakubuwono X. This building is generally in a well-maintained condition. However, many damages require immediate treatment. This research was carried out to identify damage and recommend appropriate treatment. This research uses a qualitative rationalistic method with a focus on observing physical damage in the buildings. Identification of damage becomes the basis for recommendations and handling strategies for conservation activities. The results of the research show that the Pesanggrahan Krapyak Giriwaya building has important historical, scientific, and cultural value, so it needs to be preserved. The building leaks the roof which causes damage to the wood, walls, and floor. Handling of building damage is done by replacement or repair using materials that are suitable or close to the original materials. Apart from that, damage management is carried out through a combination of the use of natural ingredients and chemicals.